A case of adult patent ductus arteriosus‐associated infective endarteritis who was successfully treated with only antibiotics. Issue 3 (14th March 2023) - Kanai, Akira; Chikata, Yuichi; Iwata, Hiroshi; Ajima, Tomohi; Kaneko, Tomohiro; Murata, Azusa; Kagiyama, Nobuyuki; Fukushima, Yoshifumi; Miyazaki, Sakiko; Minamino, Tohru
Abstract: Patent ductus arteriosus‐associated infective endarteritis (PDA‐IE) is an extremely rare complication of PDA in recent years. In this report, we describe a case of PDA‐IE complicated by septic pulmonary embolism who was successfully treated with only antibiotics. Abstract : In adults, infectious endarteritis (IE) is an extremely rare complication of PDA. Increasing awareness for IE as a complication of PDA as well as highlighting the importance of oral hygiene, particularly in adult individuals with unclosed PDA, are needed.